Analysis of genetic and phenotypic heterogeneity in juvenile polyposis. Issue 5 (1st May 2000) - Woodford-Richens, K; Bevan, S; Churchman, M; Dowling, B; Jones, D; Norbury, C G; Hodgson, S V; Desai, D; Neale, K; Phillips, R K S; Young, J; Leggett, B; et al.
Abstract : BACKGROUND: Juvenile polyposis syndrome (JPS) is characterised by gastrointestinal (GI) hamartomatous polyposis and an increased risk of GI malignancy. Juvenile polyps also occur in the Cowden (CS), Bannayan-Ruvalcaba-Riley (BRRS) and Gorlin (GS) syndromes. Diagnosing JPS can be problematic because it relies on exclusion of CS, BRRS, and GS. Germline mutations in the PTCH, PTEN and DPC4 ( SMAD4) genes can cause GS, CS/BRRS, and JPS, respectively. AIMS: To examine the contribution of mutations in PTCH, PTEN, and DPC4 ( SMAD4) to JPS. METHODS: Forty seven individuals from 15 families and nine apparently sporadic cases with JPS were screened for germline mutations in DPC4, PTEN, and PTCH . RESULTS: No patient had a mutation in PTEN or PTCH . Five different germline mutations were detected in DPC4 ; three of these were deletions, one a single base substitution creating a stop codon, and one a missense change. None of these patients had distinguishing clinical features. CONCLUSIONS: Mutations in PTEN and PTCH are unlikely to cause juvenile polyposis in the absence of clinical features indicative of CS, BRRS, or GS. A proportion of JPS patients harbour DPC4 mutations (21% in this study) but there remains uncharacterised genetic heterogeneity in JPS.